2019
DOI: 10.1039/c9ra05041h
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 nanotubes loaded with TiO2 nanoparticles for enhanced electrocatalytic hydrogen evolution

Abstract: Polarization curves of TiO2, MoS2-NTs and TiO2/MoS2-NTs in 0.5 M H2SO4 solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The higher performance of A-MoS 2 @SWCNT comes from more active sites exposed from the MoS 2 due to the introduction of SWCNT rather than SWCNT itself, which is confirmed by the poor performance of pure SWCNT. Even though the performance of A-MoS 2 @SWCNT is still inferior to the Pt/C catalyst, which has the lowest overpotential of 69 mV, the performance is comparable to recent published works related to HER performance of MoS 2 as shown in Table S1 [32][33][34][35][36][37][38][39][40][41]. After annealing at 500°C in argon, 2H-MoS 2 @SWCNT exhibits an overpotential of 277 mV, which is caused by the decrease in active sites as the basal plane being inert to HER reaction.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The higher performance of A-MoS 2 @SWCNT comes from more active sites exposed from the MoS 2 due to the introduction of SWCNT rather than SWCNT itself, which is confirmed by the poor performance of pure SWCNT. Even though the performance of A-MoS 2 @SWCNT is still inferior to the Pt/C catalyst, which has the lowest overpotential of 69 mV, the performance is comparable to recent published works related to HER performance of MoS 2 as shown in Table S1 [32][33][34][35][36][37][38][39][40][41]. After annealing at 500°C in argon, 2H-MoS 2 @SWCNT exhibits an overpotential of 277 mV, which is caused by the decrease in active sites as the basal plane being inert to HER reaction.…”
Section: Resultssupporting
confidence: 69%
“…For instances, Xie et al reported a defect-rich ultrathin MoS 2 nanosheets with a Tafel slope of 50 mV/dec [43], Ye et al showed phosphorous-doped MoS 2(1-x) P x with the Tafel slope of 57 mV/dec [44], and Luo et al designed a two-dimensional (2D) MoS 2 -confined Co(OH) 2 nanoparticle electrocatalyst with the Tafel slope of 53 mV/dec [45]. Table S1 shows the comparison of recent publications, indicating the top performance of this work [32][33][34][35][36][37][38][39][40][41].…”
Section: Energy Materials Advancesmentioning
confidence: 73%
“…The long-term durability of the electrode serves as an important factor in evaluating the electrochemical material [ 52 ]. The stability of all electrodes was evaluated by applying a current of 10 mA cm −2 through chronopotentiometry for a total of 10 h, and the results are shown in Figure 8 A.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a continuous long-term operation of 1000 cycles and a 24-h chronopotentiometry 29 , 48 50 were conducted for the 1T/2H-MoS 2 /HDGQDs sample to test its stability. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%